Parvovirus particles as platforms for protein presentation. - Miyamura, K (1994)
Empty capsids of the human pathogenic parvovirus B19 can be produced in a baculovirus system. B19 capsids are composed mainly of major capsid protein (VP2) and a small amount of minor capsid protein (VP1); VP1 is identical to VP2 but contains an additional 227-aa N-terminal region ("unique" region). A portion of that region of VP1 is external to the capsid, and VP1 is not required for capsid formation. We substituted the unique region with a sequence encoding the 147 aa of hen egg white lysozyme (HEL) and constructed recombinant baculoviruses with variable amounts of retained VP1 sequence joined to the VP2 backbone. After cotransfection with VP2 baculovirus and expression in insect cells, capsids were purified by density sedimentation. Purified recombinant capsids contained HEL. External presentation of HEL was demonstrated by immunoprecipitation, ELISA, and immune electron microscopy using anti-lysozyme monoclonal antibodies or specific rabbit antisera. Empty particles showed enzymatic activity in a micrococcal cell wall digestion assay. Rabbits inoculated with capsids made antibodies to HEL. Intact heterologous protein can be incorporated in B19 particles and presented on the capsid surface, properties that may be useful in vaccine development, cell targeting, and gene therapy.